CONTEMPORARY FORMS OF WORK WITH A DIGITAL FEATURE IN PRIVATE INTERNATIONAL LAW (EU and comparative law issues and challenges series (ECLIC), 2023)
Digitalization has enabled the rapid development of the gig economy and changed the entire paradigm in such a way that through digitalization people are increasingly achieving their primary employment. As a result, there is a frequent occurrence of the phenomenon of digital nomads and platform workers. Although initially conceived as freelance jobs, in certain cases, the legal relationships of digital nomads or platform workers take on the characteristics of an employment relationship. To circumvent fiscal and labour obligations, digital nomads or platform workers are often defined in contracts as self-employed individuals or independent contractors, resulting in a deprivation of labour rights. Consequently, a challenge arises for European private international law in terms of the correct characterization regarding the legal relationship and, subsequently, the application of the appropriate conflict of law rule to determine the applicable law.